Specificity of structure of complete mortality of individuals buried in the cemetery at the hospital and the church of Holy Spirit as compared to other cemeteries in Lublin from the 15th to 18th century - Kozak-Zychman, Wanda; Szarlip, Anna (Anthropological Review, 2015)
The goal of the study is to analyse and evaluate a complete mortality of individuals buried in the cemetery at the hospital and the church of Holy Spirit in Lublin. The main question is whether and to what extent the results of research into the subject will reflect the physical condition and the low social status of individuals from the Holy Spirit hospital-poorhouse. The comparison includes burials of Lublin burghers, church dignitaries and religious brothers and sisters of the Cathedral and Pobrygidkowski Church. This study discusses such issues as the share of children, juveniles and adults, the sex ratio, distribution of age and sex of adult and the average life span for men and women. The differences in the cumulative distributions of age frequency (dx) for the compared cemeteries were assessed using the Kolmogorov-Smirnov test. To evaluate the differences in average life span of adults the Student’s t-test was used after verification of the equality of variance by using the F-Snedecor test. The cemetery at the hospital and the church of Holy Spirit clearly stands out among comparable sites, not only in the way of burying the dead. The study of individuals buried in the Holy Spirit cemetery showed: the largest share of children and juveniles, as well as small percentage of individuals over the age of 50 years, which resulted from a low average life span for both men and women (significant differences). The comparison of the cumulative relative numbers (dx) from the interval of 10–15 year shows this percentage to be the highest and remain so up to the last interval, i.e. 60 years and more (significant differences for group 15–20 years – compared with the Cathedral and the 30–40 years – compared with the Pobrygidkowski Church). A poor physical condition, clearly related with low social status, is indicated by a variety of illnesses, injuries and malformations which were recorded in a large number of the skeletal remains, i.e. more than 70% of individuals.